ESTIMATES OF MORTALITY, POPULATION SIZE AND YIELD PER RECRUIT OF NEMIPTERUS JAPONICUS (BLOCH) IN THE TRAWLING GROUNDS OFF KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
The mortality rates of N. japonicus are estimated from annual age compositionof fish caught by trawlers. The estimated values are Z = 1.86, F = 0.72and M = 1.14. The exidoitatlon rate (U) is estimated at 0.33 and the totalannual stock at 1181 tonnes. The yield curve shows that the fishing mortality canbe increased from the present level of 0.72 to 1.75 to get increased yield.